New board of the Ibero-American Federation of Acoustics (FIA): The news is also on the new website
<span data-sheets-root="1" data-sheets-value=""1":2,"2":"The Ibero-American Federation of Acoustics (FIA) is a nonprofit civil institution, established in 1995 and registered in Spain. It is comprised of the acoustics associations of Spanish and Portuguese-speaking countries. Currently, its members are Argentina, Brazil, Chile, Colombia, Ecuador, Spain, Mexico, Portugal, Peru, Venezuela, and Uruguay. During the 12th Ibero-American Conference of Acoustics held in Florianópolis from August 28 to 31, 2022, the election and inauguration of the FIA’s board was made official for the period 2022–2026, who have already made a new website available for the entity: https://fia-acustica.org."" data-sheets-userformat=""2":15357,"3":"1":0,"5":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"6":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"7":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"8":"1":["1":2,"2":0,"5":"1":2,"2":0 ,"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"10":1,"11":4,"12":0,"14":"1":2,"2":0,"15":"Calibri","16":12">The Ibero-American Federation of Acoustics (FIA) is a nonprofit civil institution, established in 1995 and registered in Spain. It is comprised of the acoustics associations of Spanish and Portuguese-speaking countries. Currently, its members are Argentina, Brazil, Chile, Colombia, Ecuador, Spain, Mexico, Portugal, Peru, Venezuela, and Uruguay. During the 12th Ibero-American Conference of Acoustics held in Florianópolis from August 28 to 31, 2022, the election and inauguration of the FIA’s board was made official for the period 2022–2026, who have already made a new website available for the entity: https://fia-acustica.org. , number=54, journal=Acústica e Vibrações, author=Paixão, Dinara Xavier da, year=2022, month=dez., pages=181–183